2006
DOI: 10.1590/s0104-11692006000200008
|View full text |Cite
|
Sign up to set email alerts
|

A gravidez na adolescência sob a perspectiva dos familiares: compartilhando projetos de vida e cuidado

Abstract: This qualitative study aimed to apprehend the meaning of adolescents' pregnancy for their families, using semistructured interviews and collective subject discourse. Adolescent pregnancy is represented as a problem to be faced with family support. The families worry and are mobilized to solve adversities. Besides the shock about the news, impotence as to pregnancy prevention, conformism, happiness and improvement in family relationships due to the baby's arrival, participants evidenced frustration due to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
53

Year Published

2012
2012
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 5 publications
1
14
0
53
Order By: Relevance
“…A study on teenage pregnancy, from the perspective of the family, showed changes in relationships and practices among family members and pregnant teens. Family concern with physical well-being of youth and offering subsidies for care during pregnancy and after child birth is highlighted (6) . In the case of the mother, her originating role of caring permeates the established relationships in the world of life.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study on teenage pregnancy, from the perspective of the family, showed changes in relationships and practices among family members and pregnant teens. Family concern with physical well-being of youth and offering subsidies for care during pregnancy and after child birth is highlighted (6) . In the case of the mother, her originating role of caring permeates the established relationships in the world of life.…”
Section: Discussionmentioning
confidence: 99%
“…In adolescence, the situation of pregnancy interrupts projects, drives the adolescent and their families to rebuild their life plans and reflect on their experiences (6) . In contrast, discontinuation of some projects gives rise to the development of new projects, thus opening possibilities for the life of the pregnant teenager and her family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essa constatação ficou evidente em pesquisa que buscou apreender o significado da gravidez da adolescente para os familiares (Silva, Tonete, 2006), visto que, para eles, esse acontecimento familiar e social era assumido e vivenciado pela jovem, porém, com o suporte familiar, contribuindo para o desenvolvimento global da adolescente e de sua família.…”
Section: Assim Durante O Curso Da Residência Multiprofissional Em Saunclassified